Transformation of Sense of Place in Citra Niaga Area - Fitriansyah Fitriansyah; Putu Ayu P. Agustiananda; Arif Budi Sholihah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Citra Niaga area in Samarinda, a recipient of the Aga Khan Award, has experienced a significant decline in existence due to modern competition and the erosion of sense of place. This research aims to identify sense of place elements (physical form, activity, meaning) based on cross-generational perceptions to formulate an adaptive revitalization strategy. Using data (Likert scale questionnaire and qualitative) from 93 respondents (visitors and merchants), the quantitative analysis shows the historical value and original architecture of Citra Niaga is appreciated. However, significant weaknesses were seen in the diversity of activities, quality of facilities, and physical tidiness. The qualitative analysis highlighted an aspiration gap between generations: the older generation longs for the nostalgia of the past, while the younger generation seeks dynamic experiences and modern facilities. Key complaints include parking issues, cleanliness, and lack of creative events. These results emphasize the need for a holistic approach. The proposed revitalization strategy includes preserving the original architecture along with improving parking facilities and arrangements, diversifying activities through cultural events and contemporary tenants, and building a historical narrative that appeals to all generations. The goal is to transform Citra Niaga into a relevant, beloved and sustainable public space for the people of Samarinda.